High-pressure dissociation of olivine in North West Africa 7397 lherzolitic shergottite - Masashi, Yoshida; Masaaki, Miyahara; Akira, Yamaguchi; Naotaka, Tomioka; Takeshi, Sakai; Hiroaki, Ohfuji; Fumiya, Maeda; Itaru, Ohira; Eiji, Ohtani; Seiji, Kamada; Hiroki, Suga; Takuji, Ohigashi; et al. (2017)
第8回極域科学シンポジウム/個別セッション：[OA] 南極隕石 12月7日（木）国語研究所 2階講堂 The Eighth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites Thu. 7 Dec./2F Auditorium, National Institute for Japanese Language and Linguistics conference object